Management of Infrastructure in Supporting the Implementation of the Merdeka Curriculum - Septiana, Wiwin; Lian, Bukman; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2024)
Infrastructure management is the most important thing in supporting the implementation of Merdeka curriculum in schools. This study aims to describe and analyze the management of facilities and infrastructure in supporting the implementation of the Merdeka Curriculum and describe and analyze obstacles and solutions to overcome the gap in facilities and infrastructure in supporting the implementation of the Merdeka curriculum in SMP Negeri Keluang. Data collection techniques in this study used interview, observation, and documentation techniques. In the interviews, researchers involved principals, treasurers, wakasapras, and teachers. Data analysis techniques in this study include data reduction, data presentation, conclusions, and data validity using triangaluasi. This study concluded that the management of infrastructure facilities to support the implementation of the Merdeka curriculum at SMP Negeri Keluang has been carried out well by management functions. This study contributes to the principals in Indonesia to apply management of facilities and infrastructure where they would implement the Merdeka Curriculum.